Cognitive demand, digital screens and blink rate. (October 2015) - Rosenfield, Mark; Jahan, Shadika; Nunez, Kiara; Chan, Kahei
Highlights: Varying cognitive demand produced a significant reduction in blink rate. Switching to digital displays from print does not change blink rate. Contemporary screens may be closer to print than older displays. Dry eye symptoms may be related to the number of incomplete blinks. Abstract: Purpose: Many subjects experience ocular and visual symptoms when viewing digital electronic screens. Previous studies have reported a reduced blink rate during computer operation and suggested that this may account for some of the symptoms experienced during such tasks. However, it is unclear whether these changes in blink rate are related to the screen display or to differences in the mental requirements of the task. Accordingly, the present study compared blink rates when reading material having low or high cognitive demand from a tablet computer or hard copy printed text. Methods: Subjects ( N = 16) were required to perform a continuous 10 min reading task either from a tablet computer or a printed hard copy page at a viewing distance of 30 cm. Two sets of text, which varied in their level of cognitive demand, were used. Target size, contrast and viewing angle were similar for all conditions. Subjects were video-recorded during the task to determine their blink rate. Results: Varying cognitive demand resulted in a significant reduction in blink rate. While the method of presentation (tablet versus print) did not produce a significant change in blink rate, the interaction of cognition with the method of presentation was statistically significant. Conclusions: These results indicate that a change in the cognitive demand of the task has a larger effect on mean blink rate than varying the method of presentation. Contemporary screens may be closer in format to printed materials than older displays. Therefore, it seems unlikely that the ocular and visual symptoms commonly experienced when viewing digital screens are produced by a reduced blink rate.